(untitled) (Archaeologia Adriatica, 2013)
In the course of archaeological excavations at the Pakoštane-Crkvina site from 2006 to 2013, the remnants of the Church of St. Mary, which was part of the medieval settlement of Zablaće, were unearthed. Auxiliary rooms and a medieval cemetery were uncovered beside the church. However, the features of grave 75 make it stand out. It is a constructed tomb with Romanesque style characteristics. The construction of this unusual grave can be dated to the 12th century. It can be compared to the tomb of the Abbess Vekenega in the Benedictine monastery of St. Mary in Zadar. Partial reconstruction is also possible based on the preserved parts. Apart from its rich architecture, grave 75 should also be singled out for the finds uncovered within it. These include jewellery, parts of attire and coins. Grave 75 and the other unearthed graves and finds indicate the site’s importance in the period between the 12th and 16th century.